Arousal amplifies biased competition between high and low priority memories more in women than in men: The role of elevated noradrenergic activity. (June 2017) - Clewett, David; Sakaki, Michiko; Huang, Ringo; Nielsen, Shawn E.; Mather, Mara
Highlights: Arousal enhanced competition effects in memory in women with high noradrenergic activity. Men did not show such arousal-biased competition effects in memory. Under high noradrenergic activity, arousal impaired distracter recognition in women. Under high noradrenergic activity, arousal enhanced distracter recognition in men. Memory selectivity was greater in naturally cycling women with high NE/low sex hormones. Abstract: Recent findings indicate that emotional arousal can enhance memory consolidation of goal-relevant stimuli while impairing it for irrelevant stimuli. According to one recent model, these goal-dependent memory tradeoffs are driven by arousal-induced release of norepinephrine (NE), which amplifies neural gain in target sensory and memory processing brain regions. Past work also shows that ovarian hormones modulate activity in the same regions thought to support NE's effects on memory, such as the amygdala, suggesting that men and women may be differentially susceptible to arousal's dual effects on episodic memory. Here, we aimed to determine the neurohormonal mechanisms that mediate arousal-biased competition processes in memory. In a competitive visuo-attention task, participants viewed images of a transparent object overlaid on a background scene and explicitly memorized one of these stimuli while ignoring the other. Participants then heard emotional or neutral audio-clips and provided a subjective arousal rating. Hierarchical generalized linear modeling (HGLM) analyses revealed that greater pre-to-post task increases in salivary alpha-amylase (sAA), a biomarker of noradrenergic activity, was associated with significantly greater arousal-enhanced memory tradeoffs in women than in men. These sex-dependent effects appeared to result from phasic and background noradrenergic activity interacting to suppress task-irrelevant representations in women but enhancing them in men. Additionally, in naturally cycling women, low ovarian hormone levels interacted with increased noradrenergic activity to amplify memory selectivity independently of emotion-induced arousal. Together these findings suggest that increased noradrenergic transmission enhances preferential consolidation of goal-relevant memory traces according to phasic arousal and ovarian hormone levels in women.